1998
DOI: 10.1046/j.1365-2036.1998.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

High Helicobacter pylori eradication rate with a 1‐week regimen containing ranitidine bismuth citrate

Abstract: Background: High Helicobacter pylori eradication rates have consistently been reported with 2‐week dual therapy regimens of ranitidine bismuth citrate plus clarithromycin. Ranitidine bismuth citrate with two antibiotics may provide an alternative 1‐week eradication regimen. Methods: This double‐blind, randomized, parallel group, international, multicentre study compared ranitidine bismuth citrate 400 mg b.d. and clarithromycin 500 mg b.d. for 2 weeks (RC) with ranitidine bismuth citrate 400 mg b.d., clarithrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
4
16
0
Order By: Relevance
“…Our study shows that a triple regimen containing RBC plus low‐dose clarithromycin and metronidazole produces excellent eradication rates when it is given for at least 7 days. This finding confirms the good performance of previous studies with this 1‐week regimen 6 –8 and the achievement of more than 80% eradication rates on intention‐to‐treat analysis is in full accordance with the criteria of the Maastricht Consensus meeting 1 . Prolonging the treatment to 10 days does not confer any advantage in terms of eradication rates and, moreover, augments costs and side‐effects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study shows that a triple regimen containing RBC plus low‐dose clarithromycin and metronidazole produces excellent eradication rates when it is given for at least 7 days. This finding confirms the good performance of previous studies with this 1‐week regimen 6 –8 and the achievement of more than 80% eradication rates on intention‐to‐treat analysis is in full accordance with the criteria of the Maastricht Consensus meeting 1 . Prolonging the treatment to 10 days does not confer any advantage in terms of eradication rates and, moreover, augments costs and side‐effects.…”
Section: Discussionsupporting
confidence: 90%
“…In relation to the good results of 1‐week proton pump inhibitor‐based triple therapy, we have recently shown that shortening the treatment with RBC plus low‐dose clarithromycin and metronidazole to 7 days produces eradication rates as high as 86% on an intention‐to‐treat analysis 6 . This excellent performance has been confirmed by other studies adopting either the same antibiotic combination 7 , 8 or tetracycline plus clarithromycin 9 …”
Section: Introductionmentioning
confidence: 69%
“…Recently, in a European multicentre prospective randomized trial, RBC (400 mg) was co‐prescribed with clarithromycin 500 mg and metronidazole 400 mg b.d. for 1 week and compared with the standard RBC–clarithromycin dual therapy for 2 weeks in a group of dyspeptic patients 9 . The results of this study suggested that a 1‐week regimen of RBC‐based triple therapy is sufficient to cure the infection.…”
Section: Introductionmentioning
confidence: 93%
“…The results of seven day treatment arms grouped for the main combinations of antimicrobial agents are given in figures 1-3. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Is more better?…”
Section: Introductionmentioning
confidence: 99%